Single-cell analysis of myeloid cells in HPV+ tonsillar cancer - Jimenez, David Gomez; Altunbulakli, Can; Swoboda, Sabine; Sobti, Aastha; Askmyr, David; Ali, Ashfaq; Greiff, Lennart; Lindstedt, Malin (Frontiers in Immunology, 2023)
The incidence of human papillomavirus-positive (HPV+) tonsillar cancer has been sharply rising during the last decades. Myeloid cells represent an appropriate therapeutic target due to their ability to orchestrate antigen-specific immunity within the tonsil, the availability of viral antigens, and the proximity of the tumor and the underlying lymphoid tissue. However, the interrelationship of steady-state and inflammatory myeloid cell subsets, and their impact on patient survival remains unexplored. Here, we used single-cell RNA-sequencing to map the myeloid compartment in HPV+ tonsillar cancer. We observed an expansion of the myeloid compartment in HPV+ tonsillar cancer, accompanied by interferon-induced cellular responses both in dendritic cells (DCs) and monocyte-macrophages. Our analysis unveiled the existence of four DC lineages, two macrophage polarization processes, and their sequential maturation profiles. Within the DC lineages, we describe a balance shift in the frequency of progenitor and mature cDC favoring the cDC1 lineage in detriment of cDC2s in HPV+ lesions. Furthermore, we observed that all DC lineages apart from DC5s matured into a common activated DC transcriptional program involving the upregulation of interferon-inducible genes. In turn, the monocyte-macrophage lineage was subjected to early monocyte polarization events, which gave raise to either interferon-activated or CXCL-producing macrophages, the latter enriched in advanced tumor stages. We validated the existence of most of the single-cell RNA-seq clusters using 26-plex flow cytometry, and described a positive impact of cDC1, and interferon-activated DCs and macrophages on patient survival using gene signature scoring. The current study contributes to the understanding of myeloid ontogeny and dynamics in HPV-driven tonsillar cancer, and details myeloid biomarkers that can be used to predict therapy effects and assess patient prognosis.